P-077. Myxoma of bone. Review of 17 cases - Sassi, L. M. [UNESP]; Biazolla, E. R. [UNESP]; Freitas, S. E N [UNESP]; Ramos, G. H A [UNESP]; Oliveira, B. V. [UNESP] (My University, 2001)
Myxoma of bone (fibromyxoma) is a slowly growing, locally invasive tumor that almost always occurs in the facial bones. The tumor has a potential to recur, but does not metastasize. The lesion is usually painless but causes slowly progressive swelling, sometimes resulting in severe facial deformity. Aim: Review of myxoma of bone experience in two institutions. Methods: Retrospective chart review of all patients with diagnose of myxoma/fibromyxoma of bone identified in the tumor registry of two referral cancer centers: Hospital Erasto Gaerntner (HEG), Curitiba, PR Brazil and University of Sao Paulo (UNESP), Aracaatuba Campus, Sao Paulo, SP Brazil. We reviewed the age, sex, ace, presenting symptoms, topography of lesion and treatment. Results: From January 1972 to July 2000 we found 17 patients from both institutions that met the diagnostic criteria; 15 from HEG and two from UNESP. The median age was 32 years (range 10-55 years). Eleven patients were male, 14 were white and three were black. Only three patients presented with local pain, the remaining were free of symptoms, presenting only with local tumor. The tumor affected the maxilla in 11 patients (six on the right), the mandible in five and the zygomatic bone in one. All patients were treated by excisional surgery and one patient received adjuvant radiation therapy. Nine patients needed reconstruction after the tumor excision. Five of them were reconstructed with local soft tissue flaps; two received iliac crest autologous bone graft; and two had a microvascularized autologous fibula graft. Conclusion: The myxoma of bone in our experience is a rare tumor and occurs more frequently in the maxilly bone in young males. These findings are consistent with the literature data.